Effects of gender and education on social identity in Chakma tribal population in Bangladesh - Rahman, AKM Rezanur (Journal of Life and Earth Science, 2011)
Key words: Social identity; gender; tribal culture; self-categorization; education DOI: 10.3329/jles.v5i0.7359 J. Life Earth Sci., Vol. 5: 101-103, 2010